Silvopastoral systems under native forest in Patagonia Argentina - Peri, Pablo Luis; Hansen, Nidia E.; Bahamonde, Héctor Alejandro; Lencinas, María Vanessa; Von Müller, Axel Ricardo; Ormaechea, Sebastián Gabriel; Gargaglione, Veronica Beatriz; Soler Esteban, Rosina Matilde; Tejera, Luis E.; Lloyd, Carlos E.; Martínez Pastur, Guillermo José
In Patagonia, silvopastoral systems in Nothofagus antarctica (ñire) forest has become an economically, ecologically and socially productive landuse system. Patagonian experience with silvopastoral systems in the past 15 years is reviewed in this chapter. The productivity and nutritive value (crude protein content and dry matter, DM, digestibility) of understorey grassland were dependent on the interaction of environmental (mainly soil water availability and light intensity) and system level management factors. Planned thinning in secondary forest stands provide wood production and also improve the undestorey DM production by increasing incoming radiation. Within a Management Plan, two thinning intensities, depending on stand water stress conditions, are proposed. In addition, the use of Reineke’s Stand Density Index (SDI) is recommended to be used when deciding thinning intensities for different canopy covers. Livestock production is the main source of annual income from silvopastoral systems in N. antarctica forest where cattle and mixed livestock production (cattle + sheep) is the main activity. Animal performance at the whole-farm scale is described by comparing a traditional extensive grazing management with an adaptive silvopastoral management. The management factors that favor adoption of silvopastoral system are strategic separation of homogenous areas (grass steppe, forest and riparian meadows), stocking rate adjustments based on grassland net primary productivity and the protection of regeneration from herbivores browsing by using individual tree guard. Also, data from litter decomposition, nutrients dynamic and carbon storage are informed. Finally, aspects related to criteria and indicator (C&I) to assess ñire forest’s sustainability under silvopastoral use and biodiversity conservation issues are also presented. Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral. Unidad Académica Río Gallegos; Argentina. Instituto Nacional de Tecnología Agropecuaria. Centro Regional Patagonia ...